A prognosis and cost-effectiveness systematic review of non-invasive treatments for root caries - Fábio Luiz de Resende Cussi; Déborah Lousan do Nascimento Poubel; Adriano de Almeida de Lima; Ana Claudia Morais Godoy Figueiredo; Cristine Miron Stefani; Fernanda Cristina Pimentel Garcia; Nailê Damé-Teixeira (Revista da Faculdade de Odontologia de Porto Alegre)
Aim: to evaluate the prognosis of root caries treatment with non-invasive methods, as well as to compare non-invasive therapies as viable alternatives for clinicians, indicating their cost-effectiveness. Literature review: Data collected were number of active lesions at baseline(BL) and in the last clinical assessment after follow-up(FL), and the follow-up period in months(P). The outcome was the monthly progression rate of the lesions that was calculated by (FL–BL)/P. A negative progression rate means the arrestment of the lesions. A cost-effectiveness rate was calculated. Results: From 596 titles retrieved in the search, 8 studies were included in a qualitative synthesis after assessed for eligibility. The monthly progression rate of lesions of home-based treatments (toothpastes, mouth rinses, supplemented milk intake) was an average of -0.79 (-3.68 to 2.3), while the office-based treatments (varnish, topic solutions) was 0.07 (-0.01 to 0.51), suggesting a better prognosis of the home-based treatments. The lowest monthly progression rate was -3.97 (toothpaste 5000ppm/F) while the highest was 2.31 (conventional toothpaste). The cost-effectiveness rate was better for treatments with toothpastes with 5000ppm/F (BRL21.78) when compared to mouthwashes (BRL579.47). Discussion: A better prognosis was found for toothpastes with a high fluoride concentration (5000ppm/F) compared to other therapies, as well as a better cost-effectiveness when compared to mouthwashes. Conclusion: Home-based therapies represented the highest rates of good prognosis for treating root caries lesions within the available scientific evidence. Although 5000ppm/F toothpastes have a very high cost for the Brazilian market, this treatment presented the highest cost-effectiveness when compared to mouthrinses (PROSPERO:CRD42019136035).